Artificial Intelligence and Adaptation to Climate Change: Opportunities and Challenges - Nargiz Azer Hajiyeva (World Scientific Reports, 2025)
This article examines the role of artificial intelligence in combating climate change and supporting sustainable development. Artificial intelligence (AI) processes large volumes of climate data, increases the accuracy of forecasts, optimizes energy consumption, and enhances agricultural productivity. At the same time, it provides effective solutions for monitoring carbon emissions, managing renewable energy sources, and protecting ecosystems. With these features, AI makes a significant contribution to building a sustainable and environmentally friendly future.